Salivary density of Streptococcus mutans and Streptococcus sobrinus and dental caries in children and adolescents with Down syndrome - Flávia SCALIONI; Camila CARRADA; Fernanda MACHADO; Karina DEVITO; Luiz Cláudio RIBEIRO; Dionéia CESAR; Rosangela RIBEIRO
Abstract Streptococcus mutans and Streptococcus sobrinus are strongly associated with dental caries. However, the relationship between oral streptococci and dental caries in children with Down syndrome is not well characterized. Objective To assess and compare dental caries experience and salivary S. mutans, S. sobrinus, and streptococci counts between groups of Down syndrome and non-Down syndrome children and adolescents. Material and Methods This study included a sample of 30 Down syndrome children and adolescents (G-DS) and 30 age- and sex-matched non-Down syndrome subjects (G-ND). Dental caries experience was estimated by the number of decayed, missing, and filled teeth in the primary dentition and the permanent dentition. Unstimulated whole saliva samples were collected from all participants. The fluorescence in situ hybridization technique was used to identify the presence and counts of the bacteria. The statistical analysis included chi-square, Student's t-test and Spearman's correlation. Results The G-DS exhibited a significantly higher caries-free rate (p<0.001) and a lower S. mutans salivary density (p<0.001). No significant differences were found in the salivary densities of S. sobrinus or streptococci between the groups (p=0.09 and p=0.21, respectively). The salivary S. mutans or S. sobrinus densities were not associated with dental caries experience in neither group. Conclusion The reduced dental caries experience observed in this group of Down syndrome children and adolescents cannot be attributed to lower salivary S. mutans densities, as determined with the fluorescence in situ hybridization technique.